EMBEDDEDNESS AND THE (RE)MAKING OF RETAIL SPACE IN THE REALM OF MULTICHANNEL RETAILING: THE CASE OF MIGROS SANAL MARKET IN TURKEY. Issue 1 (March 2016) - Appel, Alexandra
ABSTRACT: The purpose of this article is to investigate the value of the concept of embeddedness for economic geographers. Alongside the case study of the multichannel grocery retailing brand Migros in Turkey, the spatial impacts – in relational and physical terms – of digitalization and the integration of an online shop into the profile of a supermarket chain are investigated. In applying the concept of embeddedness the article seeks to understand these complex, diverse and uneven processes of (retail) restructurings that affect different dimensions and dynamics of networks, societies and spaces. In my case study I identify two dimensions of embeddedness processes: (1) embedding the online shop in the firm's routines and practices, whereby processes of transfer of knowledge and technology dominate; and (2) embedding online shopping in the customer's routines and practices, whereby processes of adaption to consumer culture dominate. These dimensions are reflexive and as such mirror ongoing negotiation processes between the two stakeholders. On one hand multichannel retailing thus not only alters where but also how people shop, and can result in new retail spaces like pick‐up stores. On the other hand it can be shown, that the "locations", where online shopping of Migros is available, reproduce spatial variations of socio‐economic factors, such as income distribution or population density. As such, the concept of embeddedness is useful for economic geographers – also in the realm of e‐commerce – to unravel the interconnections of societal, organizational and spatial patterns as well as their variations across space. The study is based on qualitative interviews.